Selective Synthesis of Silacycles by Borane‐Catalyzed Domino Hydrosilylation of Proximal Unsaturated Bonds: Tunable Approach to 1, n‐Diols. Issue 19 (13th September 2017) - Shin, Kwangmin; Joung, Seewon; Kim, Youyoung; Chang, Sukbok
Abstract: The tris(pentafluorophenyl)boron‐catalyzed domino hydrosilylation of substrates carrying unsaturated functionalities in a proximal arrangement is presented to produce silacycles. Excellent levels of efficiency and selectivity were achieved in the cyclization by the deliberate choice of the hydrosilane reagents. The key to successful cyclic hydrosilylation is the reactivity enhancement of the second intramolecular hydrosilylation by a proximity effect. Not only dienes but also enones, enynes, ynones and enimines readily afford medium‐sized silacycles under convenient and mild conditions. The cyclization proceeds with acceptable diastereoselectivity mainly controlled by the conformational bias towards inducing additional stereogenic centers. The silacycles obtained from this reaction were converted to 1, n‐diols or 1, n‐amino alcohols upon oxidation, thus rendering the present cyclization a powerful tool for accessing synthetically valuable building blocks. Abstract :